Comparison of Dynamic Navigation and Static Navigation Systems in Implant Surgery: Accuracy and Application Analysis - Wang Nianrui (BIO Web of Conferences)
Due to the high demands for accuracy and precision in complex implant surgeries, navigation technology has gradually been applied in the field of dentistry. Although static navigation provides pre- designed surgical guides, its inability to adjust the implant pathway in real time during surgery may lead to insufficient accuracy. In contrast, the real-time monitoring and adjustment capabilities of dynamic navigation are particularly important in cases with complex anatomical structures and high aesthetic requirements, significantly reducing the risk of damaging critical anatomical structures and improving the success rate of surgeries. Factors affecting the accuracy of dynamic navigation systems include bone density, the choice of calibration method, the experience and skills of the dentists, as well as the characteristics and design of the implants. This review provides guidance for clinicians in selecting navigation systems, especially highlighting the significant advantages of dynamic navigation in the applications of edentulous implant placement and anterior aesthetic zone implantation.